Implementasi Kebijakan Undang Undang Peraturan Daerah Nomor 25 Tahun 2005 Tentang Penertiban Hewan Ternak - Moh. Ardiansah; Djaafar , Lucyane; Dahlan, Meriasusanti; M. Wantu, Sastro (Jurnal Indragiri Penelitian Multidisiplin, 2025)
This study aims to determine the extent of the implementation of Regional Regulation Number 25 of 2005 concerning the Control of Livestock in Moutong District, Parigi Moutong Regency. The research employs a qualitative approach. Data collection techniques include observation, interviews, and documentation, with both primary and secondary data sources. The findings reveal that the policy implementation has not been optimal due to a lack of seriousness from the government and enforcement team, as well as limited socialization efforts toward the community. Other inhibiting factors include low public awareness, budget constraints, and limited understanding of the policy among implementers. The conclusion of this study is that greater commitment is needed from the government and enforcement team in enforcing the regulation, along with more effective community outreach. Additionally, adjustments must be made to address obstructing factors such as funding and implementers’ comprehension, in order for the policy to be successfully executed in accordance with its original goals.